Compositional analysis of chalcopyrite using calibration-free laser-induced breakdown spectroscopy - Ahmad, A.; Hafeez, M.; Abbasi, S. A.; Khan, T. M.; Faruque, M. R. I.; Khandaker, Mayeen Uddin *; Ahmad, P.; Rafique, M.; Haleem, N. (MDPI, 2020)
Thisarticlepresentselementalanalysisofaneconomicallyimportantmineral(chalcopyrite) oflocalorigin. Calibration-freelaser-inducedbreakdownspectroscopy(CF-LIBS)methodologybased on the assumption of optically thin plasma and local thermodynamic equilibrium was employed for quantitative analysis. Plasma on the surface of the chalcopyrite target was generated by an Nd:YAG laser beam of wavelength 532 nm, pulse width 5 ns, and operated at repetition rate of 10 Hz. A LIBS2000+ detection system, comprised of ﬁve spectrometers, covering the spectral range from 200–720 nm, was used to record the signal of the optical emission from the chalcopyrite plasma. Recorded optical spectrum revealed the presence of Cu and Fe as the major elements while Ca and Na were recognized as the minor elements in the target sample. Quantitative analysis has shown that the relative concentrations of Cu, Fe, and Ca in the sample under study were 58.9%, 40.2%, and 0.9% by weight respectively. However, Na was not quantiﬁed due to the unavailability of suitable spectral lines, required for CF-LIBS analysis. Results obtained by CF-LIBS were validated by X-ray ﬂuorescence (XRF) analysis, which showed the presence of ﬁve compositional elements viz. Cu, Fe, Si, Se and Ag with weight percentages of 58.1%, 35.4%, 5.7%, 0.7%, and 0.1% respectively. These results endorse the eﬀectiveness of the CF-LIBS technique for quantitative analysis of major elements, however, its usefulness in case of minor and trace elements needs further improvement.